Comments in the Internet Media as the Reflection of National Mentality Peculiarities - Abdullina, Liliya R.; Nizamieva, Liliya R.; Nazarova, Gulnara I. (Journal of History Culture and Art Research, 2017)
The article is devoted to defining the peculiarities of national perception through the analysis of the comments taken from news media. The research is based on comparative and contrastive analysis of the reader’s comments to the articles devoted to the terroristic attack in Nice happened on July 14, 2016 and reflected in mass media in the French and Russian languages. On the first stage of the research the object of comment and the peculiarities of its representation in two languages are defined. On the second stage of the research the frame analysis of the studied material is fulfilled, consisting of defining the contextual frames. The key topical subframes, which in turn are divided into slots, are determined in the structure of frames. The logical-semantic relations are built among the structural elements of frames. The possibility of crossing topically-different subframes within one frame is demonstrated. The frequency of domination of this or that slot in comments is defined and explained. The allomorphic and isomorphic features defined in the research show the peculiarities of cultural and historical values influencing national mentality.